Finding work after 40 : proven strategies for managers and professionals - Bell, Robin McKay; Mifsud, Liam. (London : A&C Black, 2011)
In an era of economic recession, workers over forty are particularly vulnerable to layoffs and sustained unemployment. This book is the complete career survival guide for Baby Boomers, developed and road tested by a network of executive job clubs geared especially for older managers and professionals.
Keywords: Middle-aged persons -- Employment